THE USE OF DICTOGLOSS TO IMPROVE STUDENTS’ WRITING IN MUHAMMADIYAH PLUS SECONDARY SCHOOL BATAM - Zaki, Leil Badrah (Jurnal JOEPALLT (Journal of English Pedagogy, Linguistics, Literature, and Teaching), 2022)
Teaching writing in secondary school is found as another level of skill to be mastered (Abdulwahed and Ismail, 2011; Pertiwi and Drajati (2018); Ardiansyah, (2020)). Research about teaching writing at this junior high school level often got less attention which happened in Muhammadiyah Plus Secondary School Batam. However, students at this level are supposed to be able to master the writing skill as well as learn other skills in English. In implementing that, thus, a teaching method is needed to be chosen. In this study, the researcher will examine the use of Dictogloss as a technique to improve secondary students’ writing skills. Dictogloss is going to use as a treatment to help students to develop their grammar, vocabulary, spelling, and punctuation as found as the mostly error made by them. This learning which will integrate dictation given by the researcher and peer-assessment as a technique to analyse is expected to be beneficial. Hence, the aim of this study is to analyse the use of Dictogloss to improve students writing skills. The participants are the students from grade 9A, 26 students in total, in Muhammadiyah Plus Secondary School Batam. The class subject is going to be The English Cambridge exposing about Procedure Text. In order to apply the research, a Classroom Action Research (CAR) is selected as the research method to use. Keywords: dictogloss, writing skill, teaching writing, secondary students